Ferroelectrically augmented contact electrification enables efficient acoustic energy transfer through liquid and solid media - Kim, Hyun Soo; Hur, Sunghoon; Lee, Dong-Gyu; Shin, Joonchul; Qiao, Huimin; Mun, Seunguk; Lee, Hoontaek; Moon, Wonkyu; Kim, Yunseok; Baik, Jeong Min; Kang, Chong-Yun; Jung, Jong Hoon; et al. (Royal Society of Chemistry, 2022)
As demands for portable electronic devices grow, wireless energy transfer (WET) has started to become readily available. Until now, studies on WET have been mainly based on the electromagnetic (EM) induction method using EM waves. However, it is still challenging to utilize current EM wave mediated WET in those areas where it is most needed: underwater, body-implant, and EM-shielded cases (liquid/metals). Acoustic energy transfer (AET) can be an alternative to EM-wave based WET. Here, we present a simple but powerful triboelectric AET module by tuning the work function of the triboelectric layer via the large polarization of the embedded relaxor single crystal. Additionally, uniform displacement, a quasi-mode oscillation, across the flexible electrode surface in response to the square wave has improved energy transfer efficiency. A systematic investigation was conducted for energy transferring conditions of receiving angle and ferroelectric polarization. We successfully demonstrated the transmission of 8 mW electric power at a distance of 6 cm underwater, which is sufficient to use in most demanding but inaccessible areas. In addition, AET is demonstrated and discussed in both liquids (underwater and in-body), and solids (metal, wood, and plastic). We anticipate that our approach will enable current next-level AET technology to be utilized in the actual field.